Legal Reconstruction of PayLater Transactions in Marketplaces: Fiqh Muamalah and Maqasid al-Shariah Perspectives - Rizal Fajri, Yose; Atmaja, Dani (Universitas Tanjungpura, 2026)
The rapid expansion of digital marketplaces has introduced the buy now pay later (BNPL) system, enabling consumers to obtain goods through deferred payment schemes. Despite enhancing financial accessibility, this model raises significant legal concerns within Islamic jurisprudence (fiqh muamalah), particularly regarding the elements of riba (usury) and gharar (excessive uncertainty). This study aims to analyze the contractual structure of modern paylater transactions and to reconstruct a Shariah-compliant model grounded in the objectives of Islamic law (maqasid al-shariah). Employing a normative-doctrinal legal approach, this research relies on classical fiqh sources, contemporary Islamic finance literature, and relevant academic studies. The findings indicate that conventional paylater schemes resemble a loan contract generating time-based increment, thereby potentially constituting riba nasi’ah, and may involve gharar due to non-transparent cost structures and cumulative penalties. A Shariah-based reconstruction can be achieved by transforming the structure into a bai’ bi tsaman ajil contract with a fixed price agreed upon at inception, eliminating time-based interest and progressive penalties, and ensuring full contractual transparency. The maqasid framework, particularly the protection of wealth (hifz al-mal) and justice (‘adl), provides a normative foundation for designing ethical deferred payment systems in the digital economy.